A Qualitative Study on Drug Abuse Among University and Medical College Students regarding Motivations and First Encounters (Journal of Monno Medical College, 2025)
Background: The transition to higher education brings stress, social pressures, and potential for drug use as a coping mechanism. University environments can normalize drug use, while medical students face additional pressures due to their curriculum and potential for self-medication. This qualitative study explores motivations and first encounters with drugs among university and medical college students to understand how these factors contribute to drug abuse in this population.Objective:  This study employed qualitative methods to investigate the motivations and experiences that lead to initial drug use among university and medical college students. The aim is to understand how social environments, academic pressures, and potential self-medication practices among the students influence these behaviors.Methodology: This qualitative study employed thematic analysis to explore the motivations and experiences of university and medical college students in Shahbag, Dhaka, Bangladesh, who initiated drug use. Ten participants were recruited through purposive sampling, focusing on students who self-reported current drug use. Data were collected between January and July 2024.Results: Thematic analysis revealed students using drugs to cope with academic pressure and stress. Social circles normalized drug use, and students sought perceived benefits like focus improvement. First encounters varied, but peer pressure and curiosity played a role. Importantly, students acknowledged negative consequences. This study offers insights into drug abuse motivations among university and medical students.Conclusion: The study informs targeted prevention programs for universities and medical colleges. These programs should prioritize stress management, mental health support, and debunking drug-related myths to prevent initial use and reduce abuse.Journal of Monno Medical College December, 2024;10 (2):77-82